Anders denken.: Postkolonialismus, Geopolitik und Politische Geographie - Lossau, Julia (ERDKUNDE, 2000)
While the Anglo-American realm has been witnessing a reawakening interest in political geography and its explicit politicisation during the last three decades, German political geography has largely remained a minor discipline unaware of its political content. Emanating from the specific way of coming to terms with a doubtful past, its insignificance is most apparent regarding the widespread disinclination to interfere in the contemporary revitalisation of the term Geopolitik. Against this background, the paper outlines a different understanding, a more appropriate understanding it is hoped, of political geography. Taking the perspective of critical geopolitics and linking it explicitly to the field of post-colonial theory, the supposed innocence not only of disciplinary, but also of ‚popular' geographical discourse is challenged. Geopolitical reasoning, it is argued and illustrated by the representations of Turkey in German foreign policy, (re-)produces the taken-for-granted boundaries demarcating the place of the ‚self' from ‚other' places. Against this binary logic, the paper offers alternative concepts of cultural localisation and hence possible strategies of resistance.